Faktor - Faktor Yang Berhubungan Dengan Kejadian Diare Pada Balita Di Wilayah Kerja Puskesmas Bangun Purba - Junita, Elvira (Jurnal Martenity and Neonatal, 2014)
Diarrhea is defecating (fÃ¦ces defekasi) to the number greater than normal usually (100-200 mls per hour feces) with fÃ¦ces shaped a liquid or semiliquid (semisolid) accompanied with a frequency greater than three times a day.Diarrhea can be caused by a lack of maintaining healthy environment. Diarrhea is the second child mortality. This research purposes to know factor - factor That deals with the occurrence diarrhea in toddlers in the work area puskesmas get up purba.Type this research is quantitative analytic by design cross sectional.A population and sample in this research totaled 82 toddlers. Independent variable is age fives, clean environment not giving breast-fed exclusive and education mother and the dependent variable is the incident diarrhea.Data is collected used data primary use sheets checklist and analyzed test using chi-square.The result analysis age toddlers obtained value pvalue 0.005, the result analysis healthy environment obtained value pvalue 0,000, the result analysis not giving breast-fed exclusive obtained value pvalue 1,000 and the result analysis education mother obtained value pvalue 0,003. The conclusion of this research is independent variable of subjects, 4 there are three variables diarrhoea berhubungann by events in toddlers fives, namely age clean environment and education mother.The variables is not give breast-fed exclusive unconnected with 5-87s diarrhoea in toddlers.Morein expected to health workers to know the importance of giving information on mothers have about fives factors that cause of diarrhea in toddlers can reduce the risk of diarrhea in toddlers.